2010
DOI: 10.1159/000321045
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid Blood Levels in Patients with Pulmonary Tuberculosis at a Tuberculosis Referral Center

Abstract: Background: Serum concentrations of isoniazid (INH) were evaluated in Iranian patients admitted to the Tuberculosis Ward of Masih Daneshvari Hospital, Tehran, Iran. Factors correlated to plasma INH levels were determined. Methods: Blood samples were obtained 2 h after ingestion of 5 mg/kg INH in 82 patients (1 sample/patient) on days 3–15 of treatment. The following variables were investigated: INH plasma level, duration of therapy, age, sex, weight, dose of INH administered and smoking status. Results: The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…20 In a previous clinical study on INH blood concentrations, we observed low concentrations of the drug in 14.6% of patients and reported a significant correlation between INH plasma concentrations and duration of INH administration (P < 0.001), i.e., INH concentration increased with each day of treatment. 21 In the present study, low INH concentrations were found in almost half of our patients. Furthermore, the median INH serum concentration was higher in female patients than in males at 2 and 6 h post dose.…”
Section: Discussionsupporting
confidence: 44%
“…20 In a previous clinical study on INH blood concentrations, we observed low concentrations of the drug in 14.6% of patients and reported a significant correlation between INH plasma concentrations and duration of INH administration (P < 0.001), i.e., INH concentration increased with each day of treatment. 21 In the present study, low INH concentrations were found in almost half of our patients. Furthermore, the median INH serum concentration was higher in female patients than in males at 2 and 6 h post dose.…”
Section: Discussionsupporting
confidence: 44%
“…Instead, it is more likely that following the development of drug resistance to the powerful antituberculosis compounds (INH and rifampicin), subpopulations resistant to the less powerful EMB emerge due to increased selective pressure. Subtherapeutic plasma concentrations of INH in patients with a rapid acetylator status could create selective pressure that may lead to treatment failure and the emergence of drug resistance [25]. SNPs at embB 306 displayed diverse MICs of which a significant proportion (73%) was scattered along the critical concentration resulting in borderline resistance.…”
Section: Resultsmentioning
confidence: 99%
“…6,20,41 6-Gingerol in ZB is found to be effective in controlling CINV. [55][56][57] GR is a well-known TCM that is believed to be the king of herbs in the Orient, especially in China, Korea, and Japan. Ginsenosides and polysaccharides are considered to be active constituents with anticancer, antioxidant, and immunomodulation effects, which contribute to enhance immunomodulation effect against CINV.…”
Section: Discussionmentioning
confidence: 99%